Tertiary lymphoid structures and B-cell infiltration are IPF features with functional consequences - Cocconcelli, Elisabetta; Balestro, Elisabetta; Turato, Graziella; Fiorentù, Giordano; Bazzan, Erica; Biondini, Davide; Tinè, Mariaenrica; Bernardinello, Nicol; Pezzuto, Federica; Baraldo, Simonetta; Calabrese, Fiorella; Rea, Federico; et al. (Frontiers in Immunology, 2024)
Background Recent literature has shown the presence of B cells and autoantibodies in idiopathic pulmonary fibrosis (IPF) which would imply the presence of tertiary lymphoid structures (TLS, sites where the immune response is triggered), yet TLS are not considered features of the histological characteristics of IPF. Aim This study aims to quantify the presence, size, and degree of activation of TLS in biopsied and explanted lungs from patients with early- and late-IPF, never treated with antifibrotics, and relate their presence and activity to the clinical course, disease progression, and lung inflammation. Methods Immunohistochestry for B cells and CD4, CD8, and CD45 cells was performed in lung tissue from IPF patients: 18 at diagnosis (early), 39 explanted (end-stage), and 12 smoking controls. TLS activation was assessed by CD40 expression. Spirometry along 31 (12–72) months of follow-up was used to characterize end-stage IPF as slow progressors or rapid progressors. Results B cells, along with other inflammatory cells, were higher in early- and end-stage IPF than in controls (p < 0.001). In rapid progressors, all inflammatory cells were higher than in slow progressors (p < 0.05). TLS were present in 100% of early- and end-stage IPF and in 50% of controls. In end-stage IPF, the TLS area and activation score were higher than in early IPF (p < 0.0001; p = 0.005) and controls (p < 0.04; p < 0.002). TLS activation score correlated with FVC decline during follow-up in rapid progressors (r = 0.73; p = 0.007) but not in slow progressors. Conclusions A prominent B-cell infiltration, along with the presence of TLS, the activity of which correlates with FVC decline, is an important component of IPF from the beginning of the disease, likely playing an important role on its mechanism and progression.